HEAD INJURED ARMED FORCES CASUALTIES - CAN WE IMPROVE OUTCOME? - Abayadeera, A. (My University, 2012)
General Hospital Anuradhapura (GHA) is the first receiving station for the casualties of the operational areas of Mankulam, Puliyankulam, Oddusudan, Omanthe etc. Most priority 1 coded patients are directly air lifted to GHA, treated or stabilised there and thereafter either treated in GHA or transferred to the Army Hospitals or to the General Hospitals in the rest of the country. The Surgical Intensive care Unit (SICU) at GHA where most of the critically ill patients are treated consists of 5 beds and receives direct admissions from the surgical casualty ward and the operating theatres. The aim of this audit was to assess the initial and subsequent care of 'head injured' patients and their outcome in order to ascertain whether there is room for improved care